CEO Overconfidence, Corporate Governance, and R&D Smoothing in Technology-Based Entrepreneurial Firms - Huang, Yu; Wang, Xinchun; Li, Yuanqin; Yu, Xiaoyu (Frontiers in Psychology, 2022)
The intertemporal stability of research and development (R&D) investment is a key issue in successfully promoting the continuation of innovation activities under high uncertainty in entrepreneurship. R&D smoothing helps firms to navigate the uncertainties of the external environment and maintain the stability of their investments in innovation. Chief executive officers (CEOs) are the most important decision-makers in firms’ strategic planning. However, overconfident CEOs may overlook the importance of their firms’ strategic actions on innovative activities. Drawing on upper echelons theory, this paper examines how CEO overconfidence affects firms’ R&D smoothing. Using a sample of firms listed in China’s Growth Enterprises Market between 2013 and 2020, this study finds that CEO overconfidence has a significant negative impact on R&D smoothing. Furthermore, our findings reveal that firms’ internal control quality and institutional investor monitoring can mitigate the negative association between CEO overconfidence and R&D smoothing. Our findings provide new insights into the micro-level theoretical explanations for R&D smoothing and offer practical implications for technology-based entrepreneurial firms.